2007
DOI: 10.1007/s11244-007-9011-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuum and Quantum-Chemical Modeling of Oxygen Reduction on the Cathode in a Solid Oxide Fuel Cell

Abstract: Solid oxide fuel cells (SOFCs) have several advantages over other types of fuels cells such as highenergy efficiency and excellent fuel flexibility. To be economically competitive, however, new materials with extraordinary transport and catalytic properties must be developed to dramatically improve the performance while reducing the cost. This article reviews recent advancements in understanding oxygen reduction on various cathode materials using phenomenological and quantum chemical approaches in order to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 200 publications
(243 reference statements)
2
24
0
Order By: Relevance
“…[ 30,53,[78][79][80][81][82][83][84][85] To date, there are a number of good reviews that focus on electrodes for oxygen reduction reaction (ORR) in SOFCs, as listed in Table 1 . [86][87][88][89][90][91][92][93][94] The contents of these reviews can be classifi ed into three categories: ORR mechanisms, more active electrode materials, and nanostructured cathodes via infi ltration processes. However, the electrode materials covered are mainly those containing alkaline earth metal elements.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 30,53,[78][79][80][81][82][83][84][85] To date, there are a number of good reviews that focus on electrodes for oxygen reduction reaction (ORR) in SOFCs, as listed in Table 1 . [86][87][88][89][90][91][92][93][94] The contents of these reviews can be classifi ed into three categories: ORR mechanisms, more active electrode materials, and nanostructured cathodes via infi ltration processes. However, the electrode materials covered are mainly those containing alkaline earth metal elements.…”
Section: Reviewmentioning
confidence: 99%
“…Solid oxide fuel cell cathodes: Polarization mechanisms and modeling of the electrochemical performance [107] 2004 Factors governing oxygen reduction in solid oxide fuel cell cathodes [105] 2004 Factors controlling the oxide ion conductivity of fl uorite and perovskite structured oxides [86] 2007 Continuum and quantum-chemical modeling of oxygen reduction on the cathode in a solid oxide fuel cell [87] 2007 Electrode materials and reaction mechanisms in solid oxide fuel cells: a brief review [88] 2010 Oxygen transport in perovskite and related oxides: A brief review [89] 2010 Oxygen reduction and transportation mechanisms in solid oxide fuel cell cathodes [106] 2012 Electrochemistry of mixed oxygen ion and electron conducting electrodes in solid electrolyte cells [91] 2013 Gas transport in porous electrodes of solid oxide fuel cells: A review on diffusion and diffusivity measurement [92 ] 2013 Combined theoretical and experimental analysis of processes determining cathode performance in solid oxide fuel cells [112] 2014 Chromium deposition and poisoning of cathodes of solid oxide fuel cells -a review [165] 2014 Oxygen transport in perovskite-type solid oxide fuel cell materials: Insights from quantum mechanics [93] Materials for cathodes 2006 Recent developments in Ruddlesden-Popper nickelate systems for solid oxide fuel cell cathodes [349] 2008 Development of lanthanum strontium manganite perovskite cathode materials of solid oxide fuel cells: A review [127] 2009 Materials design for perovskite SOFC cathodes [45] 2009 Cathode materials for solid oxide fuel cells: A review [131] 2009 Progress in understanding and development of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ -based cathodes for intermediate-temperature solid-oxide fuel cells: A review [132] 2010 Advances in layered oxide cathodes for intermediate temperature solid oxide fuel cells [183] Nano-structured cathodes…”
Section: Mechanisms Related To Cathodes 2003mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 For the best performance in state-of-the-art applications, LSM is mixed with ionic conductors (such as, e.g., yttria-stabilized zirconia) to form composite cathodes. 3 Alternatively, dense thin film LSM electrodes are proposed for micro-SOFCs operating at temperatures below 1000 K. 4 The development of highly efficient SOFCs relies on the fundamental understanding of the ORR process at the electrode/electrolyte interface.…”
mentioning
confidence: 99%
“…In a recent exhaustive review, Choi et al reported the recent advancements in understanding oxygen reduction on various cathode materials using phenomenological and quantum chemical approaches in order to develop novel cathode materials with high catalytic activity toward oxygen reduction [27]. The authors suggest that the oxygen reduction barrier is the energetic difference between the adsorption energy (i.e.…”
Section: Resultsmentioning
confidence: 99%